2016
DOI: 10.1093/nar/gkw515
|View full text |Cite
|
Sign up to set email alerts
|

Triplex structures induce DNA double strand breaks via replication fork collapse in NER deficient cells

Abstract: Structural alterations in DNA can serve as natural impediments to replication fork stability and progression, resulting in DNA damage and genomic instability. Naturally occurring polypurine mirror repeat sequences in the human genome can create endogenous triplex structures evoking a robust DNA damage response. Failures to recognize or adequately process these genomic lesions can result in loss of genomic integrity. Nucleotide excision repair (NER) proteins have been found to play a prominent role in the recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…In vertebrates, cyclin E binds to and activates CDK2 and then promotes the G1 to S phase transition. Cyclin A binds to CDK1 and activates G2 phase [ 19 ]. In this study, we found that overexpression of MEF2A increased CDK2 but not CDK1 protein expression ( Fig 3G and 3H ), resulting in promoted G1 to S phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…In vertebrates, cyclin E binds to and activates CDK2 and then promotes the G1 to S phase transition. Cyclin A binds to CDK1 and activates G2 phase [ 19 ]. In this study, we found that overexpression of MEF2A increased CDK2 but not CDK1 protein expression ( Fig 3G and 3H ), resulting in promoted G1 to S phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…T triplex recognition in the process of DNA repair. It was shown that triplex-forming oligonucleotides are able to activate DNA recombination and DNA repair in addition to inducing genomic instability [77]. Intact p53 C-terminus is necessary for recognition of damaged DNA and recombination intermediates [2, 3, 7, 8, 63, 78, 79].…”
Section: Discussionmentioning
confidence: 99%
“…where they probed the relevant NER proteins required for recognition of the triplex structures. [ 18 ] It was found that triplex structures created with TFOs perturb the stability of the replication fork, which can ultimately cause the fork to collapse, and induce double strand breaks (DSBs), unless recognized and repaired by the cell. [ 18 ] Cells deficient in XPA and XPC, particularly XPC, have been found to accumulate DSBs after triplex formation compared to cells proficient in NER.…”
Section: Tfos and Dna Repairmentioning
confidence: 99%